Generation Z as a critical question mark for sustainable tourism – An exploratory study in Portugal - Micaela Pinho; Sofia Gomes (Journal of Tourism Futures, 2024)
Purpose – Much has been speculated about the role that Generation Z will play in achieving more sustainable development. The tourism sector gains a special role in this discussion. On the one hand, tourism, due to its growing importance, has had a significant impact on environmental sustainability. On the other hand, Generation Z will be the largest group of travellers ever in the future. In this context, the objective of the present study is to explore the interest of young Portuguese generation Z in sustainable development goals (SDGs), tourism sustainability (TS) and their pro-environmental habits and how these categories influence the choice of sustainable tourism destination. Design/methodology/approach – An online questionnaire was used to collect data from a sample of 305 young Portuguese. The quantitative analysis was performed with the application of the partial least square (PLS) model. Findings – Overall, the authors found that despite our respondents showing an interest in the SDGs the same interest is not true for tourism. Although most respondents are concerned about choosing a sustainable destination, they do not care about keeping destinations sustainable, nor do they have pro-environmental habits. Originality/value – This study presents the first evidence of the attitudes, beliefs and pro-environmental habits of Portuguese Gen Zers and their potential contribution to TS.